How does the break-junction quasiparticle tunnel conductance look like for d-wave superconductors? - Gabovich, Alexander M.; Voitenko, Alexander I. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2017)
The bias-voltage, V, dependences of the differential tunnel conductance G(V) = dJ/DV were calculated for the quasiparticle current J flowing in the ab plane across the break junction made of d-wave superconductors. The tunnel directionality effect was taken into account by introducing an effective tunneling cone described by the angle 2θ0. It was shown that G(V) looks like predominantly d-wave or isotropic s-wave ones, depending on the magnitude of θ0 and the rotation angles of the crystal lattices of electrodes with respect to the junction plane. In certain configurations, the G(V) dependences of nominally symmetric S–I–S junctions may turn out similar to those for non-symmetric S–I–N junctions (here, S, I, and N denote superconductors, insulators, and normal metals, respectively) and provide misleading information about the actual energy gap. At finite temperatures, sub-gap structures appear, which possess features appropriate to both d- and s-wave superconductors and are dependent on the problem parameters.